Komisi Nasional Ideologi Pancasila (Komnas Ideologi Negara): Sebuah Pemikiran - Yudhie Haryono (Budapest International Research and Critics University, 2017)
This paper explain about the need of establishment of Board of Pancasila as Ideology National Commission in Indonesia. The existance of this national commission is a must and significant because Pancasila is the spirit foundation of Indonesia State. The fact in Indonesia’s history and till now, the threat to change Pancasila as ideology still exist. Beside that, Pancasila as ideology will fade away in the next generation if there is no support from the govermnent to establish a state body of this issue.